Study on the Electromigration Organization and Mechanical Properties of Sn2.5Ag0.7Cu0.1RE/Cu Solder Joints - Yuming Wang; Keke Zhang; Chao Zhang; Fupeng Huo; Yijie Gao (Metals)
In this study, we designed and manufactured an ideal electromigration testing device for soldering joints to solve the reliability problems caused by temperature and current density changes in the electromigration processes of micro solder joints. We analyzed the effects of temperature and current density on the electromigration β-Sn (single-crystal β-Sn grain) of Sn2.5Ag0.7Cu0.1RE/Cu solder joints, the relationship between the grain orientation and interfacial IMC (intermetallic compound) growth of Sn2.5Ag0.7Cu0.1RE/Cu solder joints, and the mechanical properties of solder joints. The results showed that the angle θ between the c-axis of the β-Sn grain and the current direction for the Sn2.5Ag0.7Cu0.1RE/Cu solder joint gradually decreased to 8.2° when the temperature increased to 150 °C, which accelerated the diffusion of Cu atoms and Cu substrate dissolution. The recrystallization and grain growth of Cu6Sn5 (An intermetallic compound formed by the fusion of copper and tin in a ratio of six to five) grains in the anode region promoted electromigration polarity. Compared with the initial state, the shear strength decreased to 11 MPa, a decrease of 61.3%, the fracture position shifted from the top of the IMC at the cathode interface to the root of the IMC at the cathode interface, and the fracture mode changed from ductile fracture to brittle fracture. With an increase in the current density to 1.1 × 104 A/cm2, θ decreased to 3.2°. In addition, we observed the recrystallization of Cu6Sn5 grains in the anode region and an increase in the grain length and diameter to 6.8–31.9 μm, which further promoted electromigration polarity. Compared with the initial state, the shear strength decreased by 72.5% to 7.8 MPa, and the fracture position shifted from the top of the IMC at the cathode interface to the root of the IMC at the cathode interface. Additionally, the fracture mode changed from ductile to brittle fracture.